2010
DOI: 10.1007/s11240-010-9771-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of rol genes in transgenic soybean (Glycine max L.) leads to changes in plant phenotype, leaf morphology, and flowering time

Abstract: Soybean (Glycine max L.) cultivar NARC-4 was transformed with constructs carrying rolA, rolB, or rolC genes, each under the control of the Cauliflower Mosaic Virus 70S promoter. Cotyledonary nodes of soybean seeds were infected with Agrobacterium tumefaciens strain LBA4404 carrying one of the three rol genes, along with nptII in the plasmid pLBR. The efficiency of the transformation varied slightly among the three constructs, with frequencies of 6, 7, and 5% for the rolA, rolB, and rolC genes, respectively, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Consequently, it is not only necessary to develop new technologies to create germplasm resources but also breed new cultivars. Many reports showed that genetic transformation of plants with Agrobactrium rhizogenes can be used as an efficient way of breeding new cultivars for improvement and creation of germplasm resources (Zia et al 2010). So far, hairy roots which grows rapidly with stable and comparatively high content in secondary metabolites, induced by genetic transformation of A. rhizogenes, were successfully used for the production of essential oils from medicinal or aromatic plants, such as Rose-scented geranium (Pelargonium sp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is not only necessary to develop new technologies to create germplasm resources but also breed new cultivars. Many reports showed that genetic transformation of plants with Agrobactrium rhizogenes can be used as an efficient way of breeding new cultivars for improvement and creation of germplasm resources (Zia et al 2010). So far, hairy roots which grows rapidly with stable and comparatively high content in secondary metabolites, induced by genetic transformation of A. rhizogenes, were successfully used for the production of essential oils from medicinal or aromatic plants, such as Rose-scented geranium (Pelargonium sp.)…”
Section: Introductionmentioning
confidence: 99%
“…So far, hairy roots which grows rapidly with stable and comparatively high content in secondary metabolites, induced by genetic transformation of A. rhizogenes, were successfully used for the production of essential oils from medicinal or aromatic plants, such as Rose-scented geranium (Pelargonium sp.) (Saxena et al 2007), Plumbago indica (Gangopadhyay et al 2010) and Psoralea drupacea (Fabaceae) (Lystvan et al 2010) and for improvement and creation of germplasm for Nierembergia scoparia (Godo et al1997), Kalanchoe blossfeldiana (Christensen et al 2008) and Glycine max (Zia et al 2010). The transgenic plants also produced from hairy roots are usually non-chimeric because the hairy roots originate from single cells and each hairy root consists of uniformly transformed cells.…”
Section: Introductionmentioning
confidence: 99%
“…The development of transgenic Taxus cells needs an efficient genetic transformation method. The Agrobacterium-mediated transformation system has been commonly applied to engineer many plant species for desirable traits (Li et al 2008;Gelvin 2009;Raffeiner et al 2009;Silva et al 2009;Banyai et al 2010;Espasandin et al 2010;Ma et al 2010;Zia et al 2010). This system is favored over other methods, such as particle bombardment, due to the integration of low numbers of the transgene into the genome, the stability in the host cells, and the high transformation efficiency, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports showed that genetic transformation of plants with Agrobactrium rhizogenes can be used as an efficient way of breeding new cultivars for improvement and creation of germplasm resources. 5 So far, hairy roots which grow rapidly with stable and comparatively high content in secondary metabolites, induced by genetic transformation of A. rhizogenes, were successfully used for the production of essential oils from medicinal or aromatic plants, such as Rose-scented geranium (Pelargonium sp. ), 6 Plumbago indica 7 and Psoralea drupacea (Fabaceae) 8 and for improvement and creation of germ-plasm for Nierembergia scoparia, 9 Kalanchoe blossfeldiana 10 and Glycine max.…”
Section: Introductionmentioning
confidence: 99%
“…), 6 Plumbago indica 7 and Psoralea drupacea (Fabaceae) 8 and for improvement and creation of germ-plasm for Nierembergia scoparia, 9 Kalanchoe blossfeldiana 10 and Glycine max. 5 The transgenic plants also produced from hairy roots are usually non-chimeric because the hairy roots originate from single cells and each hairy root consists of uniformly transformed cells. To date, there are only a few reports on breeding transgenic P. cablin plants with pest resistance by genetic transformation with A. tumefaciens.…”
Section: Introductionmentioning
confidence: 99%